2022
DOI: 10.21608/tsnj.2022.235660
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Head Nurses' Paternalistic Leadership on Hospital Cynicism and Job Performance among Intensive Care Nurses: A Comparative Study

Abstract: Background: Paternalistic leadership is a style of leadership in which the leader merges strict discipline with the empathy of a paternal figure and moral character in a personalized climate to enable nurses perform more effectively and efficiently and help them reduce cynical behaviour toward the hospital. Aim of the study: Compare influence of head nurses' paternalistic leadership on hospital cynicism and job performance among intensive care nurses at Tanta Main University Hospitals and EL-Mehalla General Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…It may be due to corona virus crisis and its consequences of work overload. This result is agreed with Barmanpek et al (2022) (36) , Abou Shaheen and Mahmoud (2021) (37) , Elsherbeny and El-Masry (2018) (39) who found the majority of staff nurses had low level of job satisfaction. On the other side, Zakiyah et al (2021) (40) found that about sixty percent of nurses had moderate level of job satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…It may be due to corona virus crisis and its consequences of work overload. This result is agreed with Barmanpek et al (2022) (36) , Abou Shaheen and Mahmoud (2021) (37) , Elsherbeny and El-Masry (2018) (39) who found the majority of staff nurses had low level of job satisfaction. On the other side, Zakiyah et al (2021) (40) found that about sixty percent of nurses had moderate level of job satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…But almost all of studied nurses have a higher perception about interactivity dimension, followed by more than four-fifth of studied nurses have a higher perception about personal traits dimension. This result was supported by (Mahmoud and Shaheen, 2022) indicated that more than two thirds of the studied nursing personnel were high level Staff communication. And these results at the same line with study that conducted by (Newman et al, 2020).…”
Section: Discussionsupporting
confidence: 65%
“…Moral leadership embodies exceptional character, self-control, and altruism. It has been recognized that moral nurse leadership upholds high ethical standards [15].…”
Section: Introductionmentioning
confidence: 99%